2018
DOI: 10.1038/s41598-018-32861-w
|View full text |Cite|
|
Sign up to set email alerts
|

Liposome co-incubation with cancer cells secreted exosomes (extracellular vesicles) with different proteins expressions and different uptake pathways

Abstract: We recently showed that in vitro incubation of cells with liposomes of varying compositions can increase exosome secretion and increase the yield of harvested exosomes (extracellular vesicles, EVs). This might foster their potential therapeutic implementations. In the current study, we investigated the surface proteins and the uptake of the harvested exosomes (EVs) to see if the incubation of cells with liposomes would change the biological properties of these exosomes (EVs). Interestingly, exosomes (EVs) indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
(77 reference statements)
0
22
0
Order By: Relevance
“…Exosome pellet was obtained through 20,000 × g centrifugation, stored at 4 • C in Phosphate Buffered Saline (PBS 1x) and characterized with NanoSight NS300 following the manufacturer's protocol (Malvern Instruments). Quantitative determination of the exosomal markers annexin A2 (Biocompare, Cat# OKEH05627) and flotillin-1 (Antibodies online, Cat# ABIN415105) (Emam et al, 2018) was performed in the exosomal pellet by using commercial ELISA kits. Electron microscopy for size and morphology evaluations (2000× magnification) was used, as described by Maisto et al (2019).…”
Section: Exosomes Isolation and Characterizationmentioning
confidence: 99%
“…Exosome pellet was obtained through 20,000 × g centrifugation, stored at 4 • C in Phosphate Buffered Saline (PBS 1x) and characterized with NanoSight NS300 following the manufacturer's protocol (Malvern Instruments). Quantitative determination of the exosomal markers annexin A2 (Biocompare, Cat# OKEH05627) and flotillin-1 (Antibodies online, Cat# ABIN415105) (Emam et al, 2018) was performed in the exosomal pellet by using commercial ELISA kits. Electron microscopy for size and morphology evaluations (2000× magnification) was used, as described by Maisto et al (2019).…”
Section: Exosomes Isolation and Characterizationmentioning
confidence: 99%
“…76 Also, Miki et al reported a substantial contribution of CD9 in the amplification of cancer invasiveness 77 and Emam and coworkers evidenced the importance of this tetraspanin in the cellular uptake of exosomes. 78 As exosomes originate from the inversely budded membrane of the endosome and are highly enriched in CD9 and CD63 tetraspanins, we investigated the effects of the PvD 1 peptide on the content of CD9 and CD63 in MCF-7 exosomal membranes. MCF-7 isolated vesicles were characterized by TEM, western blot, DLS, and flow cytometry (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…70 Liposomes formed the basis of a study involving exosome delivery of proteins to cancer cells, where they were co-incubated with a murine melanoma cell line (B16BL6). 27,28 The liposomes used for co-incubation were either fluid DOPE-based (1,2-dioleoyl-sn-glycero-3-phosphoethanolamine) or solid HSPC-based (hydrogenated soy phosphatidylcholine). Exosomes were collected and isolated from the culture media, their protein contents analyzed and broken up into categories (tetraspanins, heat shock proteins, enzymes and others).…”
Section: Loading Of Exogenous Cargomentioning
confidence: 99%
“…The resulting exosomes were then delivered to the B16BL6 melanoma cell line, as well as a murine colorectal cancer cell line (C26), and analyses were performed for studying how exosomal expression of the different proteins impacted their uptake by cancer cells. 27 The ability to incubate liposomes with cancer cells to produce exosomes with specific proteins could be highly useful for therapeutic delivery.…”
Section: Loading Of Exogenous Cargomentioning
confidence: 99%